Timed insemination of suckled beef cows after ovulation synchronizationwith Cosynch + CIDR - Johnson, Sandra K.; Harmoney, Keith R.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Lactating beef cows (n=360) were synchronized using the Cosynch procedure; 100 μg of GnRH (day −7) followed in 7 days by 25 mg of PGF2α (day 0). A used intravaginal progesterone insert (CIDR-B) was inserted on day −7 and removed at the time of PGF2α administration. Cows were assigned to a 2 × 2 factorial arrangement of four treatments: 1) insemination beginning at 48 vs. 60 hours after PGF2α and 2) administration of a second, 100 μg injection of GnRH or an equivalent volume of saline immediately after timed AI. Timed AI at either 48 or 60 hours after PGF2α in a Cosynch + CIDR protocol was equally effective. Administration of GnRH at timed AI improved conception in all cycling cows and in some noncycling cows, depending on their progesterone status.
Keywords: Beef; Ovulation synchronization; Beef cows; Timed AI; GnRH; CIDR